2022
DOI: 10.1002/app.52394
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of antimicrobial poly(lactic‐co‐glycolic acid)/silk fibroin/aloe anthraquinone fibrous membranes for potential application of wound healing

Abstract: Antibacterial wound dressings can kill bacteria around the wound and then accelerate the wound healing. To fabricate an antibacterial membrane for potential application of wound healing, poly(lactic-co-glycolic acid) (PLGA), silk fibroin (SF), and natural antimicrobial agent aloe anthraquinone (AA) were blended for electrospinning. The electrospun PLGA/SF/AA fibrous membrane consists of smooth and uniform fibers with an average diameter of 583 ± 112 nm. The stress of the PLGA/SF/AA fibrous membrane is 3.88 ± 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…PLGA alone has a relatively low mechanical strength, while PLLA addition may enhance the strength of the resultant composite, thereby protecting the wound from external stimuli. [20][21][22][23] Tannic acid (TA) is a plant polyphenol with excellent antimicrobial properties. 24 Several studies have found that TA has antibacterial, antioxidant, anti-inflammatory, and hemostatic properties, which are beneficial for accelerating wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…PLGA alone has a relatively low mechanical strength, while PLLA addition may enhance the strength of the resultant composite, thereby protecting the wound from external stimuli. [20][21][22][23] Tannic acid (TA) is a plant polyphenol with excellent antimicrobial properties. 24 Several studies have found that TA has antibacterial, antioxidant, anti-inflammatory, and hemostatic properties, which are beneficial for accelerating wound healing.…”
Section: Introductionmentioning
confidence: 99%